A retrospective assessment of the hydrological conditions of the Samborombón coastland (Argentina) - Carol, E.S. (2014)
Coastal wetlands are transitional zones that play an important role as buffers between the land and sea in several ways, such as protecting the land from storm surge and reducing the input of nutrients from surrounding watersheds to the sea. Understanding the influence of human activities on the hydrological conditions of coastal wetlands is of paramount importance for preserving the ecological function and biodiversity of these unique ecosystems. In the last century, the Samborombón coastland (Argentina), which is an extensive intertidal wetland, has been affected by hydraulic projects and human activities. In this study, through a retrospective assessment of the hydrologic conditions, we show the impacts of channelization, embankments and mining on the surficial and groundwater hydrology of the Samborombón wetlands. The results indicate that channelization has promoted tidal flooding and seawater encroachment along the channels. The embankments have separated large areas from the estuary tides; during heavy rainfalls, they act as obstacles and cause the inundation of inland regions while allowing the accumulation of sodium chloride by saltwater evaporation after tidal overtopping events. The freshwater resources in the aquifer of the paleo-coastlines have been seriously damaged by mining of the shell ridges. The halophyl vegetation in the marshlands and the native forest of the shell ridges, which depend on tidal flow and fresh water, respectively, have been threatened. Nevertheless, although the hydrology of the Samborombón coastland has undergone changes, the engineering projects did not permanently modify or damage the surrounding ecosystems. The outcomes of this study will be useful for remediating ecosystems that have been impacted by human activities by following the fundamentals of ecological engineering.